Implementation of Six Sigma in Glucose POCT Quality Control at Dr. Soetomo General Academic Hospital - Susi Oktaviani; M. Robiul Fuadi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Point of Care Testing (POCT) is important for the examination of critically ill patients in the emergency room and intensive care unit. The evaluation of the analytic quality of POCT is needed to ensure the quality of patient care at Dr. Soetomo General Academic Hospital. The purpose of this study is to evaluate the analytical quality of POCT at Dr. Soetomo General Academic Hospital. This was an observational analytical study that was done at Dr. Soetomo General Academic Hospital Surabaya in July 2017. Point of care testing quality analysis was based on 20 within run Internal Quality Control (IQC). Internal quality control data was used to calculate the mean, SD, and CV%. CV% was calculated with the following equation